On Solidarity: Gramsci’s Objectivity as a Corrective to Buber’s I-It - Ryan Adams (Rosenberg & Sellier, 2017)
I and Thou sets out a dichotomy of human interactions between the merely objective I-It and the intense intersubjective relationship of the I-Thou, creating a problem of how one is to differentiate the I-It relations that are healthy and natural, and those that are limiting and detrimental. As a corrective to this ambiguity, I posit the principle of solidarity as a relation which retains the personhood of the Other yet still confines it to what Buber calls the I-It “relation”. To do this I will discuss similar attitudes such as sympathy and camaraderie using them to draw out the meaning of solidarity in contradistinction to them, and show how solidarity functions as Gramsci’s Objectivity.